USING ARTIFICIAL INTELLIGENCE IN THE DEVELOPMENT OF BANKING SERVICES (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This thesis examines the theoretical and methodological foundations, practical aspects, and economic efficiency of using artificial intelligence technologies in the development of banking services. Amidst the rapid development of the digital economy, rising demand for financial services, and intensifying competition between banks, artificial intelligence technologies are becoming one of the primary tools for modernizing the banking sector.
Keywords: Artificial intelligence, banking services, digital banking, FinTech, machine learning, Big Data, credit scoring, risk management, chatbots, digital transformation, cybersecurity.